2013
DOI: 10.1016/j.neuro.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib alters microtubule polymerization and axonal transport in rat dorsal root ganglion neurons

Abstract: Bortezomib is part of a newer class of chemotherapeutic agents whose mechanism of action is inhibition of the proteasome-ubiquitination system. Primarily used in multiple myeloma, bortezomib causes a sensory-predominant axonal peripheral neuropathy in approximately 30% of patients. There are no established useful preventative agents for bortezomib-induced peripheral neuropathy (BIPN), and the molecular mechanisms of BIPN are unknown. We have developed an in vitro model of BIPN using rat dorsal root ganglia neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 27 publications
10
77
1
Order By: Relevance
“…When evaluating cultured sensory neurons exposed to bortezomib, we observed a clear alteration in the arborization of the neurons, as previously described (Staff et al 2013). The neurites were thinner and their processes were shorter than in control neurons.…”
Section: Cytoskeleton Alterations Induced By Bortezomibsupporting
confidence: 78%
See 3 more Smart Citations
“…When evaluating cultured sensory neurons exposed to bortezomib, we observed a clear alteration in the arborization of the neurons, as previously described (Staff et al 2013). The neurites were thinner and their processes were shorter than in control neurons.…”
Section: Cytoskeleton Alterations Induced By Bortezomibsupporting
confidence: 78%
“…Values are expressed as mean and SEM. *p \ 0.05 Neurotox Res higher than the ones of our study (Staff et al 2013). However, a previous study already demonstrated that embryonic and adult DRG neurons had different sensitivity to bortezomib (Meregalli et al 2013).…”
Section: Methodsological Differences Between In Vitro Studiescontrasting
confidence: 67%
See 2 more Smart Citations
“…In the past, rodent sensory neurons/DRG have allowed important studies of the mechanisms of peripheral neurotoxicity/degeneration [45,46]. However, the overwhelming majority of reports in this area focused on the underlying mechanisms and never compared more than three toxicants.…”
Section: Discussionmentioning
confidence: 99%